AN INTEGRATED ANP-DEMATEL METHOD BASED ON THE HESITANT BIPOLAR-VALUED NEUTROSOPHIC SETS AND THEIR APPLICATION TO COASTAL EROSION - NOOR AZZAH AWANG (UNIVERSITI MALAYSIA TERENGGANU, 2022)
Analytic network process (ANP) and decision-making trial and evaluation laboratory (DEMATEL) are two commonly used multi-criteria decision making methods in the literature. The integration between these two methods has been widely investigated thanks to their mutual compatibility and the fascinating advantages that both offers. However, it was noticed that the DEMATEL-based ANP (DANP) method was not exposed to the indeterminacy and uncertainty problems. Therefore, this study aims to extend the DANP method based on the hesitant bipolar-valued neutrosophic set. In order to achieve this main objective, firstly, the hesitant bipolar-valued neutrosophic set is proposed to deal with the indeterminacy, hesitancy and bipolar judgmental thinking in the decision-making problem. The basic operational laws, union, intersection and complement for hesitant bipolar-valued neutrosophic elements are defined. Secondly, this research established a hesitant bipolar-valued neutrosophic Shapley normalized weighted Bonferroni mean (HBN-SNWBM) operator to improve the traditional approaches that have neglected the significance of the interrelationship among the aggregated arguments and their coalitions. Along with the proposed aggregation operator, this research investigated and proved their desirable properties such as commutativity, monotonicity, idempotency and boundedness.